Determinan Tingkat Kemiskinan Di Provinsi Aceh Periode 2017-2021 - Prameswari, Dea; Arif, Muhammad (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
This study aimed to estimate the effect of the Human Development Index, Education Level, Provincial Minimum Wage, Open Unemployment Rate, and Expenditure per Capita on Poverty Level in Aceh Province 2017-2021 period. The data used is secondary data obtained from the Aceh Central Statistics Agency (BPS). This study uses a quantitative approach with panel data regression analysis method. The results showed that the best model chosen was the Random Effect Model (REM). The effect validity test (t test) explains that the human development index, provincial minimum wage, and per capita expenditure have a negative and significant effect on the poverty level in Aceh Province 2017-2021 period.